Connecting to power: Political connections, innovation, and firm dynamics - Ufuk Akcigit; Salomé Baslandze; Francesca Lotti (Federal Reserve Bank of Atlanta, 2020)
How do political connections affect firm dynamics, innovation, and creative destruction? To answer this question, we build a firm dynamics model, where we allow firms to invest in innovation and/or political connection to advance their productivity and to overcome certain market frictions. Our model generates a number of theoretical testable predictions and highlights a new interaction between static gains and dynamic losses from rent-seeking in aggregate productivity. We test the predictions of our model using a brand-new dataset on Italian firms and their workers. Our dataset spans the period from 1993 to 2014, where we merge: (i) firm-level balance sheet data, (ii) social security data on the universe of workers, (iii) patent data from the European Patent Office, (iv) the national registry of local politicians, and (v) detailed data on local elections in Italy. We find that firm-level political connections are widespread, especially among large firms, and that industries with a larger share of politically connected firms feature worse firm dynamics. We identify a leadership paradox: when compared to their competitors, market leaders are much more likely to be politically connected but much less likely to innovate. In addition, political connections relate to a higher rate of survival, as well as growth in employment and revenue, but not in productivity - a result that we also confirm using a regression discontinuity design.
Keywords: O30; O43; 330; firm dynamics; innovation; political connections; creative destruction; productivity